A Synthesis of Six and Seven-membered Heterocyclic Molecules Containing an Adamantyl Fragment and an X-ray Crystal Structure of (E)-N-(adamantan-1-yl)-1-(3-nitrophenyl)methanimine - Ahmed Shukkur (مجلة بغداد للعلوم, 2020)
Our work included a synthesis of three new imine derivatives—1,3-thiazinan-4-one, 1,3-oxazinan-6-one and 1,3-oxazepin-4,7-dione—which contained an adamantyl fragment. These were produced via the condensation of the Schiff`s base (E)-N-(adamantan-1-yl)-1-(3-aryl)methanimine with 3-mercaptopropanoic acid; 3-chloropropanoic acid; and maleic, citraconic anhydride, respectively. These new imines were prepared via the condensation of adamantan-1-ylamine and 3-nitro-, 3-bromobenzaldehyde in n-BuOH. We obtained a good yield of products. FTIR, 1H NMR spectroscopy and C.H.N.S analysis were used to diagnostic the products. The molecular structure of (E)-N-(adamantan-1-yl)-1-(3-nitrophenyl)methanimine was confirmed by X-ray crystallography analysis.